中长链甘油三酯食用油对单纯性肥胖人群体脂的影响 Effect of medium-and long-chain triglycerides edible oil on body fat in individuals with simple obesity - 何定留，凡亚云，韦丽琴，吴小云，陈志敏，高红兰 HE Dingliu, FAN Yayun, WEI Liqin, WU Xiaoyun, CHEN Zhimin, GAO Honglan (Zhongguo youzhi)
旨在为中长链甘油三酯（MLCT）食用油在临床的合理应用提供依据，将106名单纯性肥胖人群随机分为两组，分别以MLCT食用油和长链甘油三酯（LCT）食用油（葵花籽油）替换家中日常食用油，每人每日30 g，连续食用60 d，观察两组人群给药前后各肥胖相关指标的变化。结果表明：两组人群在基线时体质量、身体质量指数（BMI）、腰围、臀围、体脂、皮下脂肪厚度、基础代谢、内脏脂肪面积、血糖、甘油三酯、总胆固醇、高密度脂蛋白胆固醇（HDL-C）以及低密度脂蛋白胆固醇（LDL-C）之间，差异无统计学意义(p>0.05)；给药60 d后，MLCT组人群的体质量、BMI、腰围、臀围、体脂、皮下脂肪厚度、内脏脂肪面积较给药前显著下降(p<0.05)；LCT 组人群的体脂、部分部位皮下脂肪厚度、舒张压及LDL-C较给药前显著降低(p<0.05)；与LCT组比较，MLCT组人群的腰围、臀围、体脂、部分部位皮下脂肪厚度、LDL-C给药前后的差值具有显著差异(p<0.05)。综上，MLCT食用油可以显著降低单纯性肥胖人群的体脂、腰围、臀围、皮下脂肪厚度。 To provide a basis for the rational clinical application of medium-and long-chain triglycerides (MLCT) edible oil, 106 simple obese individuals were randomly divided into two groups, and they were instructed to replace their daily cooking oil with either MLCT oil or long-chain triglycerides (LCT) oil (sunflower seed oil) at a dose of 30 g per person per day for 60 consecutive days. Changes in obesity-related indicators before and after administration were observed in both groups. The results showed that there were no statistically significant differences in body weight, BMI, waist circumference, hip circumference, body fat, subcutaneous fat thickness, basal metabolism, visceral fat area, blood glucose, triglyceride, total cholesterol, HDL-C and LDL-C between the two groups at baseline (p>0.05). After 60 d of administration, body weight, BMI, waist circumference, hip circumference, body fat, subcutaneous fat thickness and visceral fat area in MLCT group significantly decreased compared with those before administration (p<0.05). Body fat, partial subcutaneous fat thickness, diastolic blood pressure and LDL-C in the LCT group significantly decreased compared with those before administration (p<0.05). Compared with the LCT group, there were significant differences in waist circumference, hip circumference, body fat, partial subcutaneous fat thickness and LDL-C before and after administration in the MLCT group (p<0.05). In conclusion, MLCT edible oil can significantly reduce the body fat, waist circumference, hip circumference and subcutaneous fat thickness in individuals with simple obesity.